Analysis Implementation Beginning Pattern Management Finance Body Service General Area To Sustainability Service Bolo Health Center - Eni Andriani; Menap Menap; Lalu Abdul Khalik; Saimi Saimi; Sastrawan Sastrawan; Lalu Sulaiman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Puskesmas is a community health center that provides integrated services in addition to promoting the community's equal participation. To enhance the effectiveness and efficiency of these centers, the government has provided opportunities for funding through BLUD, following Presidential Decree Number 30 of 1991 and Minister of Home Affairs Decree Number 92 of 1993. However, the implementation of BLUD has not been without challenges such as difficulties in creating financial reports based on Financial Accounting Standards (SAK) due to unclear formats and transaction data flow. This research aims to identify problems in implementing the Bolo Community Health Center BLUD financial management pattern and suggest potential solutions. The research method used was qualitative, utilizing observation sheets, interview guides, and documentation sheets for data collection and analysis. The findings indicate that the implementation of BLUD at the Bolo Community Health Center has not been optimal due to limited human resources and intervention from the District Health Service. The remuneration system also does not comply with the Minister of Home Affairs Regulation. However, BLUD implementation provides budget flexibility and the ability to use the budget immediately for infrastructure and facilities to provide health services to those in need. Training on BLUD and software ownership should be provided to address these challenges to increase human resources.